1996
DOI: 10.1093/oxfordjournals.alcalc.a008221
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Alcoholism and Their Role in Therapy

Abstract: In recent years, the term 'chronic alcoholism' has had a meaning that is more descriptive than diagnostic. Several subtypes of alcoholism have been established and are now a necessary tool for studying therapy outcome. Alcohol-dependent patients can be subtyped based on clearly assigned dimensions (e.g. biological, sociological and psychological disturbances). Craving and the underlying disturbance must be treated. The number of pharmacological agents that may reduce alcohol intake has increased recently. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(90 citation statements)
references
References 11 publications
1
72
1
16
Order By: Relevance
“…Because of their large variability in a number of alcohol-related traits and behaviors, selectively bred alcohol-preferring rat lines are often seen as possible experimental models of the different types, or typologies, of human alcoholics [1,3,8,19]. According to this hypothesis and taking into account the results of the EPM [4,17] and SI [present study] experiments, alcohol-preferring P and sP rats might represent proper models for those typologies of alcoholics in whom alcohol drinking is primarily driven by a search for anxiety relief [20,21].…”
Section: Discussionmentioning
confidence: 96%
“…Because of their large variability in a number of alcohol-related traits and behaviors, selectively bred alcohol-preferring rat lines are often seen as possible experimental models of the different types, or typologies, of human alcoholics [1,3,8,19]. According to this hypothesis and taking into account the results of the EPM [4,17] and SI [present study] experiments, alcohol-preferring P and sP rats might represent proper models for those typologies of alcoholics in whom alcohol drinking is primarily driven by a search for anxiety relief [20,21].…”
Section: Discussionmentioning
confidence: 96%
“…A distribuição dos tipos de alcoolismo encontrados no presente estudo pode ser comparada com os dados de literatura, principalmente aqueles obtidos em população atendida em ambulatório 17 . As diferenças regionais encontradas também poderiam ser devidas a erros na 4 ressaltaram a importância da correta classificação dos diferentes subtipos de alcoolismo. Esses autores indicam que a correta observância da árvore decisória de classificação necessita ser seguida para homogeneização dos resultados.…”
Section: Discussionunclassified
“…No atendimento dos pacientes diagnosticados como alcoolistas são observados distintos quadros clínicos. A variabilidade observada na intensidade da síndrome de abstinência alcoólica (SAA), nos resultados terapêuticos com medicações ou com psicoterapia, na prevenção da recaída, e também nos diferentes resultados de estudos genéticos com alcoolistas, mostra que diferentes vulnerabilidades biológicas aos efeitos do álcool podem existir [3][4][5][6][7] . Reconhecer as diferenças e individualizar o tratamento é importante para se obter sucesso terapêutico.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A different approach to the classification of alcoholism was suggested by Lesch et al 53,54 . On the basis of a 5-year study including 444 patients, they suggested division into four categories based on family heredity, psychopathology and hypothetical neurobiological basis.…”
Section: Subtypes Of Alcoholismmentioning
confidence: 99%